Reconciliation and Transitional Justice in Macedonia, Ten Years Later - Ljubomir, D. FrÄkoski (Mediterranean Journal of Social Sciences, 2011)
Main hypothesis of the text is: that Reconciliation process in every post conflicting situation is relatively independent of thesuccess of the normative , and institutional arrangement of the agreement for peace . The reconciliation will have to be negotiated andimplemented with parallel ,separate structure of measures , political will and monitoring system to be successful. Second hypothesis is: thatsuccessful reconciliation could be paradoxically victim of the success of the institutional part of the agreement for peace (case of Macedonia).What produce structural problem of long-term stabilization of the country in question